1901 Idaho Sess. Laws 117, 120, § 37 pt. 17 - (:unkn) unknown (My University, 1901)
Amended the Boise city charter to allow the regulation and prohibition on the use of guns, pistols, and firearms, firecrackers, bombs, and detonating works of all description.
Keywords: DISCHARGE